IMPLEMENTATION OF EXTRA-CURRICULAR EDUCATOR POLICIES IN AN EFFORT TO IMPROVE STUDENTS’S UNDERSTANDING OF THE KORAN AT SDN SOUTH LABUHANBATU REGENCY - Syafaruddin Syafaruddin; Mesiono Mesiono; Aziddin Harahap (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
The Qur'an must be seen as a role model in various aspects of life, not only regarding dogmatic teachings, but also in science. One of the branches of science is education. The purpose of this study is to analyze the implementation of the policy of extra-curricular educators in increasing students' understanding of the Islamic religious scriptures at SDN South Labuhanbatu Regency. This study seeks to obtain complete and in-depth information about the implementation of the BTQ program policy in South Labuhanbatu Regency. Therefore, researchers used this type of research with a qualitative approach with an analytic descriptive method. The data analysis was carried out by describing the data obtained with words or sentences separated into categories to obtain conclusions. The results showed that the implementation of extracurricular teaching staff policies in an effort to improve students' understanding of the Islamic religious scriptures at SDN Labuhanbatu Selatan Regency was categorized as very good, this was indicated by (1) the implementation of the policy as of May 2018, including coordination, monitoring, and evaluation of performance. teacher; and (2) Each month the teaching staff receive an honorarium of Rp. 1,500,000 from the South Labuhanbatu Regency government and are given training every six months and all honorarium teachers use the syllabus given by the South Labuhanbatu Regency Education Office.